(untitled) (Research, Society and Development, 2021)
The effect of prosthetic abutment type on single-screwed prostheses in posterior mandibular molar rehabilitations is not yet known. Thus, the aim of this study was to evaluate the distribution of stresses in the crowns, prosthetic components, implant and bone in implant-supported restorations with or without a prosthetic abutment, maintaining an equal total height of the implant-crown set. Virtual 3-dimensional (3D) finite element models were constructed, the models were designed to represent a posterior single crown rehabilitation with a screwed retention system and external hexagon implants placed in the lower first molar region. Two rehabilitation methods were designed to simulate a monolithic zirconia crown screwed onto a conical abutment, which was screwed onto an external hexagon implant (M1); and a monolithic zirconia crown screwed directly onto the external hexagon implant using an UCLA abutment (M2). An axial load of 200 N was simulated and applied axially in the occlusal region of the restoration divided into 5 points. The quantitative and qualitative description of the maximum principal stress for crowns, von Mises stress for screws, conical abutment and implant; and minimal principal stress for cortical and medullary bone were evaluated. M1 presented similar stress distribution for crowns, cortical and medullary bone compared to M2. Conversely, the stress values were considerably higher for crowns screw and implants in the M2 group. In conclusion, single implant-supported rehabilitations of mandibular first molars using external hexagon implants presented better stress distribution on the crown screw and implants for the M1 group compared to M2.